Ocean‐scale footprint of a highly mobile fishing fleet: Social‐ecological drivers of fleet behaviour and evidence of illegal fishing. Issue 3 (16th May 2021) - Collins, Claire; Nuno, Ana; Benaragama, Aloka; Broderick, Annette; Wijesundara, Isuru; Wijetunge, Dilhara; Letessier, Tom B.
Abstract: Managing the footprint of highly mobile fishing fleets is increasingly important due to continuing declines in fish populations. However, social‐ecological drivers for fisher behaviour remain poorly understood for many fleets globally. Using the Sri Lankan fleet as a case study, we explored the role of social, environmental and policy drivers of effort distribution and illegal fishing. We used semi‐structured interviews and participatory mapping with 95 fishers, combined with explanatory modelling (GLM) and multivariate statistics, including principal component analysis (PCA). Our findings highlighted the broad footprint (~3, 800, 000 km 2 ) of this fleet, with fishing effort expended in high seas (53.9%), domestic (40.9%) and, illegally, in foreign waters (5.2%). Twenty‐six per cent of fishers directly admitted to fishing illegally in foreign waters during interviews, whereas 62% of fishers indicated doing so during participatory mapping. GLMs explained underlying decisions of where to fish (36% of the total deviance in effort distribution) as a function of social variables (14%), notably distance from landing sites (13%), and environmental variables (11%), notably sea surface temperature (10%). Multivariate analysis revealed that individual fisher characteristics associated with illegal fishing, such as a level of reliance on sharks, vary across the fleet. The analysis of qualitative data suggested that the influence of interpersonal and community social networks and perceptions of higher catch value, particularly of sharks, may be important. Our approach demonstrated the utility of mixed methods research, including the collection of qualitative data, for creating a detailed understanding of spatial behaviour, including decisions of whether to fish illegally. Results highlighted the importance of adopting a social‐ecological lens to investigate drivers for human behaviour and non‐compliance with rules. We advocate for a nuanced approach to monitoring and managing of fleets, including investigating localised social drivers for illegal fishing and enhancing regional transparency in fleet monitoring. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. සාරාංශය: මත්ස්‍ය ගහණයන්හි අඛණ්ඩ පහත වැටීම හේතුවෙන්, අධික ලෙස සංචරණය වන ධීවර යාත්‍රා සමූහ වල මං සලකුණු කළමනාකරණය කිරීම අතිශයින් වැදගත් වේ. කෙසේ වෙතත් බොහෝ ධීවර යාත්‍රා සමූහ සඳහා, ධීවරයන්ගේ හැසිරීම කෙරෙහි සමාජ‐පාරිසරික පෙළඹවීමේ සාධක බලපෑම් සිදු කරන ආකාරය පිළිබඳව ගෝලීය වශයෙන් එතරම් අවබෝධයක් නොමැත. සිද්ධි අධ්‍යයනයක් ලෙස ශ්‍රී ලාංකික ධීවර යාත්‍රා සමූහය භාවිතා කරමින්, ශ්‍රම විභජනය සහ නීතිවිරෝධී ලෙස මසුන් ඇල්ලීම සඳහා වන සමාජ, පාරිසරික හා ප්‍රතිපත්තිමය පෙළඹවීමේ සාධක වල කාර්යභාරය අපි ගවේෂණය කළෙමු. පැහැදිලි ව්‍යුහාත්මක ආකෘති නිර්මාණය (සාමාන්‍ය රේඛීය ආකෘති, GLM) සහ බහුකාර්ය සංඛ්‍යානය ඇතුළු ප්‍රධාන සංරචක විශ්ලේෂණය (PCA) සමඟ ඒකාබද්ධව, ධීවරයින් 95 දෙනෙකු සමඟ අර්ධ ව්‍යුහගත සම්මුඛ සාකච්ඡා සහ සහභාගීත්ව සිතියම්කරණය අප විසින් භාවිතා කරන ලදී. අපගේ සොයාගැනීම්, මෙම ධීවර යාත්‍රා සමූහයේ පුළුල් මං සලකුණු (~3, 800, 000 km 2 ) ඉස්මතු කර පෙන්වන අතර ගැඹුරු මුහුදේ (53.9%), ශ්‍රී ලංකාවට අයත් මුහුදු කලාපයේ (40.9%) සහ නීතිවිරෝධී ලෙස විදේශීය මුහුදු කලාප වල (5.2%) මසුන් ඇල්ලීම සඳහා ඔවුන් තම ශ්‍රමය වැය කර ඇත. සම්මුඛ සාකච්ඡාවන් හිදී ධීවර‍යින්ගෙන් 26% ක් නීතිවිරෝධී ලෙස විදේශීය මුහුදු කලාප වල මසුන් ඇල්ලීම සිදු කල බව ඍජුවම පිළිගත් අතර සහභාගීත්ව සිතියම්කරණයේදී ධීවර‍යින්ගෙන් 62% ක් එසේ කල බවට දක්වා ඇත. සාමාන්‍ය රේඛීය ආකෘති වලින් (GLMs) පැහැදිලි වන්නේ මසුන් ඇල්ලිය යුතු ස්ථාන පදනම් වන තීරණ (ශ්‍රම විභාජනයේ සම්පූර්ණ අපගමනතාවයෙන් 36% ක්), සමාජීය විචල්‍යයන් (14%), විශේෂයෙන් ගොඩබෑමේ ස්ථාන වල සිට දුර (13%) සහ පාරිසරික විචල්‍යයන් (11%), විශේෂයෙන් මුහුදු මතුපිට උෂ්ණත්වයෙහි (10%) ප්‍රතිඵලයක් ලෙසටය. බහුවිධ විශ්ලේෂණයෙන් හෙළි වූ කරුණක් වන්නේ, නීතිවිරෝධී මසුන් ඇල්ලීම හා සම්බන්ධ, මෝරුන් මත යැපීමේ ප්‍රමාණය වැනි තනි පුද්ගල ධීවර ලක්ෂණ, යාත්‍රා සමූහය පුරා වෙනස් වන බවය. ගුණාත්මක දත්ත විශ්ලේෂණයන් යෝජනා කරන්නේ, අන්තර් පුද්ගල සහ ප්‍රජා සමාජ ජාල වල බලපෑම සහ ඉහල වටිනාකමක් සහිත විශේෂයෙන් මෝරුන් වැනි මසුන් පිළිබඳ සංජානනය වැදගත් විය හැකි බවයි. නීතිවිරෝධී මසුන් ඇල්ලීම ඇතුළු අවකාශීය හැසිරීම් පිළිබඳ සවිස්තරාත්මක අවබෝධයක් ඇති කර ගැනීම සඳහා ගුණාත්මක දත්ත රැස් කිරීම ඇතුළු, මිශ්‍ර ක්‍රම පර්යේෂණ වල උපයෝගීතාව අපගේ ප්‍රවේශය මගින් ප්‍රදර්ශනය කෙරේ. මිනිස් හැසිරීම් සඳහා වන පෙළඹවීමේ සාධක සහ නීතිරීති වලට අනුකූල නොවීම විමර්ශනය කිරීම සඳහා සමාජ‐පාරිසරික කාචයක් භාවිතා කිරීමේ වැදගත්කම ප්‍රතිඵල මගින් ඉස්මතු කරයි. අපි, නීතිවිරෝධී ලෙස මසුන් ඇල්ලීම සම්බන්ධයෙන් දේශීය වශයෙන් වූ සමාජීය පෙළඹවීමේ සාධක විමර්ශනය කිරීම සහ ධීවර යාත්‍රා සමූහ අධීක්ෂණය කිරීමේදී කලාපීය විනිවිදභාවය ඉහළ නැංවීම ඇතුළුව යාත්‍රා සමූහ අධීක්ෂණය හා කළමනාකරණය කිරීම සඳහා නව ප්‍රවේශයක් යෝජනා කරන්නෙමු.